The Representation of Prophetic Messages in Folklore of Tegal Regency - Qomariyah, U um; Doyin, Mukh.; Zuliyanti, Zuliyanti; Prabaningrum, Dyah (Universitas Semarang, 2018)
Statement of the problem in this research was The Representation of Prophetic Messages in Folklore of Tegal Regency . Long time ago, folklore was used as a medium of communication between parents and their children in teaching Javanese values. Here are some messages and values in every folklore delivered in communities constructed particular character building in every communities. That message has mediated social and transcedental dimensions, it is well known as prophetical ethics which enhance humanization, liberalization, and transcendence. This research was qualitative approach regarding the description. Several studies related to substance of folklore have been conducted by some researchers are Duija (2005), Martinoska (2005), Lukin (2008), Hukantaival (2012), Galieva (2015), Taylor (2003), and Malik (2018).